Chevalierinol A and B, two new neolignan sesquiterpenoids from Magnolia chevalieri. Issue 21 (2nd November 2021) - Ninh, Pham Thi; Ha, Chu Thi Thu; Thai, Tran Huy; Hanh, Nguyen Phuong; Khang, Nguyen Sinh; Dung, Nguyen Thi; Hoai, Ly Thi Thu; Chien, Tran Van; Loc, Tran Van; Nhu, Vo Thi Quynh; Anh, Nguyen The; Hung, Trieu Quy; et al.
Abstract: Two new neolignan sesquiterpenoids, chevalierinol A (1) and chevalierinol B (2), were isolated from the ethyl acetate extract of Magnolia chevalieri leaves, together with twelve known compounds (3–14). Their structures were elucidated by analysis of spectroscopic data including 1D, 2D and mass spectra and compared with the reported data. Compounds 1, 3, 4, 6, 7, 10 were evaluated for their inhibitory effect against lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW264.7 macrophage cells. Graphical Abstract: